SIGHAT TAKLIK TALAK DITINJAU DARI HUKUM PERJANJIAN - Akhmad Shodikin; Ubaidillah Ubaidillah; Muhamad Aip Syaripuddin (IAIN Syekh Nurjati Cirebon, 2021)
Sighat taklik talak is said to be an agreement, which a husband uttered after the execution of the Nikah Act which is already in the Deed of Marriage regarding the promise of divorce which is suspended to the circumstances which may occur in the future. Because it is considered that there is no element of justice that should exist in a treaty, from which the writer feels it is necessary to try to analyze the relationship of the not-talak position of the law of the Covenant, for the sake of a family of sakinah, mawaddah and rahmah. The result of this study: the position of talak talak if viewed from the Law of the Civil Code Law found there was no suitability of the provisions of an agreement in article 1313 which describes an agreement executed by two or more persons, while the talak taklik included a unilateral agreement, in accordance with article 1320 regarding the terms of an agreement to point 2 and article 1329 regarding a person's ability to enter into an agreement, if viewed from the Civil Code, Taklik talak is not an agreement in general then there is no special impact for those who do not perform talak talak in this case is not binding.